2022
DOI: 10.1038/s41379-022-01139-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neoadjuvant therapy on PD-L1 expression and CD8+lymphocyte density in non-small cell lung cancer

Abstract: PD-L1 expression is the routine clinical biomarker for the selection of patients to receive immunotherapy in non-small cell lung cancer (NSCLC). However, the application and best timing of immunotherapy in the resectable setting is still under investigation. We aimed to study the effect of chemotherapy on PD-L1 expression and tumor infiltrating lymphocytes (TILs), which is to date still poorly understood. Our retrospective, single-centre neoadjuvant cohort comprised 96 consecutive patients with NSCLC resected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…5 One possible explanation is the fact that PD-L1 expression in NSCLC is not static but seems to undergo dynamic changes. [5][6][7][8][9] Previous studies found that PD-L1 expression may be influenced by several factors including Interferon-γ and other cytokines release, [10][11][12] activation of oncogenic drivers 6 13 and specific drugs. 14 Some studies even showed that oncological treatment may alter PD-L1 expression.…”
Section: Open Accessmentioning
confidence: 99%
“…5 One possible explanation is the fact that PD-L1 expression in NSCLC is not static but seems to undergo dynamic changes. [5][6][7][8][9] Previous studies found that PD-L1 expression may be influenced by several factors including Interferon-γ and other cytokines release, [10][11][12] activation of oncogenic drivers 6 13 and specific drugs. 14 Some studies even showed that oncological treatment may alter PD-L1 expression.…”
Section: Open Accessmentioning
confidence: 99%
“…In this issue of Modern Pathology, Zens et al 8 provide further insights into the role of predictive immune biomarkers in operable NSCLC. Specifically, they investigated the effect of neoadjuvant chemotherapy on PD-L1 expression and CD8+ TILs density in a retrospective cohort of NSCLC patients.…”
mentioning
confidence: 99%
“…Considering their results (manual scoring of clone SP263 on paired samples) and their review of the literature, the authors conclude that it seems unlikely that neoadjuvant chemotherapy induces PD-L1 expression. In view of the potential importance of this conclusion, it must be emphasized that a broadly held consensus has yet to emerge (summarized in Table 1 by Zens et al 8 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations